The Strategy of Link and Match between Higher Education Quality and The Demand for The Need of Job Field to Produce Qualified Human Resources - Sedarmayanti, Sedarmayanti (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2002)
The global era has brought the consequences and important change to the development especially in developing technology and the change of human behavior. Entering the early millennium, the manin challenge being faced to increase the competition power is how to intensify the creativity, innovation, and independent spirit which is the main focus in forming the competition power. In accordance with this case, it is necessary to create the Human Resources with a wide perspective, processing constructive vision and mission, full of creativity and innovation. To create the qualified Human Resouces, it requires the ability of mastering skills and knowledge and attitude to do the work in the office, consequently the work productivity is high and able to face the chance and challenge. In facing the competitive global life, hopefully the process of education can develope the ability to compete, to develop crative and innovative attitude and always try to incraese the quality.